Flow pattern and vascular resistive index as predictors of malignancy risk in thyroid follicular neoplasms - De Nicola, Harley [UNIFESP] (2005)
Objectives. The purpose of this study was to evaluate whether flow pattern and resistive index (RI) are useful parameters for distinguishing benign from malignant thyroid follicular neoplasms (FNs), Methods. Eighty-six thyroid nodules that underwent sonographically guided fine-needle aspiration and were diagnosed as cases of FIN were evaluated by power and duplex Doppler sonography. Pathologic correlation was available for all nodules. The flow pattern seen via power Doppler examination was ranked for each nodule on a scale of 0 to 4, in increasing flow order. For each nodule, the RI value was considered the average of 1 to 3 values obtained with different flow signals. Results. Ten nodules (11.63%) were malignant Q follicular carcinomas, 5 follicular variants of papillary carcinoma, and 2 papillary carcinomas). Fourteen nodules (16.27%) were adenomas, and 62 (72%) were non-neoplastic nodules. The average RI in non-neoplastic nodules was 0.588 (P <.001, chi(2) test): 0.662 in adenomas and 0.763 in malignant nodules. None of the nodules had flow pattern type 0. Flow patterns 1 and 2 (peripheral flow only or predominantly) were present in 58 non-neoplastic nodules (93.5%), 10 adenomas (71.4%), and 2 malignant nodules (20%). Flow pattern type 3 (predominantly central flow) was present in 7 malignant nodules (70%), 4 adenomas (28.6%), and 4 nonneoplastic nodules (6.5%). Only 1 nodule, a papillary carcinoma, had flow pattern type 4 (internal flow only). Conclusions. In FNs, there were significant positive associations between predominantly central flow and malignancy and between predominantly peripheral flow and benign disease (P <.0001, Fisher exact test). However, power Doppler characteristics could not be used to rule out malignancy because 20% of malignant nodules had predominantly peripheral flow. For predicting malignancy, an RI cutoff of 0.75 had good accuracy, specificity and negative predictive value but had low sensitivity and positive predictive value (respectively, 91%, 97%, 92%, 40%, and 67%). Resistive index values in non-neoplastic nodules were lower than in adenomas and malignant nodules (P <.001, chi(2) test).